The car industry and climate change: A historical review - Mattias Näsman; Grace Ballor (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2024)
In the second half of the twentieth century, the car industry became a lightning rod for debates about human contributions to climate change. Widespread motorisation galvanised the green movements of the 1960s and 1970s, regulators increasingly demanded the use of pollution and climate mitigation technologies, and carmakers responded to this changing consumer and regulatory environment by gradually observing stricter emissions standards and innovating away from combustible engines at the turn of the millennium. This paper traces the arc of the relationship between car manufacturing and climate change through a business historical lens, from the development of internal combustion engines and their alternatives to the political economy of an energy transition and the decision to prioritise electric vehicles. Our analysis aims to lay a foundation for further research on industry and climate change.
Keywords: 330; environmental history; business history; automakers; regulation; climate governance